Relapse in schizophrenia: Definitively not a bolt from the blue - Spaniel, Filip; Bakstein, Eduard; Anyz, Jiri; Hlinka, Jaroslav; Sieger, Tomas; Hrdlicka, Jan; Görnerová, Natálie; Höschl, Cyril (Neuroscience letters, 2018)
Detailed study of the period before schizophrenic relapse when early warning signs (EWS) are present is crucial to effective pre-emptive strategies. To investigate the temporal properties of EWS self-reported weekly via a telemedicine system. EWS history was obtained for 61 relapses resulting in hospitalization involving 51 patients with schizophrenia. Up to 20 weeks of EWS history per case were evaluated using a non-parametric bootstrap test and generalized mixed-effects model to test the significance and homogeneity of the findings. A statistically significant increase in EWS sum score was detectable 5 weeks before hospitalization. However, analysis of EWS dynamics revealed a gradual, monotonic increase in EWS score across during the 8 weeks before a relapse. The findings-in contrast to earlier studies-suggest that relapse is preceded by a lengthy period during which pathophysiological processes unfold; these changes are reflected in subjective EWS.
Keywords: dospělí; Recurrence; Relapse; průzkumy a dotazníky; Female; Telemedicine; Early warning signs; prodromální symptomy; Adult; ženské pohlaví; Surveys and Questionnaires; Schizophrenic Psychology; lidé; Information technology; recidiva; schizofrenie; retrospektivní studie; sekundární prevence; Male; Secondary Prevention; Prodromal Symptoms; Prevention; Schizophrenia; chronická nemoc; mužské pohlaví; Chronic Disease; schizofrenie (psychologie); Retrospective Studies; Humans